View Fishermen's Perception of Fish Worth Catching at The Fish Landing Site Kuala Sorkam Central Tapanuli Regency North Sumatra Province - Limbong, Irwan; Ariani, Fitri; Rosmasita, Rosmasita (Agrikan Jurnal Agribisnis Perikanan, 2021)
The fishing equipment used in Central Tapanuli Regency is dominated by gill net fishing equipment. This research was conducted in July at the Fish Landing Site Kuala Sorkam Central Tapanuli Regency, North Sumatra. The research object used in this research is gillnet fishermen located in TPI Kuala Sorkam as resource persons, the fishermen are distinguished into fishermen, skippers and crew. The equipment used in this research is data collection devices, communication devices and laptops. The operation process of Gill Net fishing equipment has four stages, namely determining the location of fishing gound, net installation, net withdrawal, and the final process of moving the catch into the hold. Perception of Gill Net fishermen in TPI Kualla Sorkam generally fall into the "medium" category more than 50% of fishermen in that category try to comply with existing regulations but fishermen's knowledge of the size of fish worth catching is still lacking.